PENGARUH THE ANTI BULLYING AND TEASING PROGRAM TEMA KOMUNITAS DALAM MENURUNKAN FREKUENSI PERILAKU BULLYING DI KELAS TAMAN KANAK-KANAK - Dinardinata, Adi; Kumara, Amitya (Jurnal Psikologi, 2015)
The purpose of this study was to determine the influence of The Anti Bullying and Teasing Program Community Theme to decrease bullying behavior in kindergarten classroom. This study involved two classroom from the same kindergartens with total 27 children in both classroom. Teachers and kindergarten involved in this study all agreed to engage in the research, and also to not apply any other similar programs in their school and classrooms. All of the teachers in both classroom had already had more than three years teaching experience. The untreated control group with removed treatment design was applied in this study to determine the program’s influence. The program was conducted based on The Anti Bullying and Teasing Book for Preschool Classroom, had six hours of intensive orientation activities for the teachers and ten sessions of community theme activity to be implemented by the teachers in their classroom. Results suggest that The Anti Bullying and Teasing Prgoram Community Theme did decrease bullying behavior.